Improving Mathematics Learning Outcomes through Problem Based Instruction - Rahayu, Ni Kadek Linda Astiti; Agustika, Gusti Ngurah Sastra (Universitas Pendidikan Ganesha, 2020)
The main problem in this study refers to the students that have a low mathematics learning outcome. This is caused by the lack of application of relevant learning models in the mathematics learning process. This study aimed to analyze the effect of the Problem Based Instruction model on the mathematics learning outcomes of fifth-grade students. This research is a quasi-experimental research using the Non-Equivalent Control Group Design which in its pretest is only used to determine group equality. Cluster technique was used to determine the research sample until 2 groups were selected consisting of the experimental group and the control group with a total sample of 87 students from a total of 8 population members with a total number of students 243. The test description was chosen as an instrument for data collection to obtain the score, analyzed by analysis techniques inferential statistics use the formula of variance separated in the t-test. Based on the results of the analysis, t count > t table is 7.2909> 2.021. So H0 is rejected and Ha is accepted. Thus, it can be concluded that the Problem Based Instruction model has a positive effect on the learning outcomes of students.